2017
DOI: 10.4103/2249-4863.222024
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of using the urine dipstick test by patient self-assessment for urinary tract infection screening in spinal cord injury patients

Abstract: Aims:The aim of this is to evaluate the reliability of the urine dipstick test by patients’ self-assessment for urinary tract infection (UTI) screening and to determine the validity of urine dipstick test.Settings:Rehabilitation Department, Srinagarind Hospital, Thailand.Study Design:A diagnostic study.Subjects and Methods:This study compared the urine dipstick test (index test) with the National Institute on Disability and Rehabilitation Research (NIDRR) criteria (gold standard test) in spinal cord injury (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Further, the present study investigated the level of agreement between nitrite and leucocyte esterase with urine culture. The agreement levels of nitrite and leucocyte esterase reported by this study were higher than those reported in Thailand [6]. In the present study, the highest agreement with urine culture was recorded for nitrite alone 87.65% (kappa = 0.351), followed by “nitrite-positive or leucocyte esterase results” 72.49 (kappa = 0.290).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Further, the present study investigated the level of agreement between nitrite and leucocyte esterase with urine culture. The agreement levels of nitrite and leucocyte esterase reported by this study were higher than those reported in Thailand [6]. In the present study, the highest agreement with urine culture was recorded for nitrite alone 87.65% (kappa = 0.351), followed by “nitrite-positive or leucocyte esterase results” 72.49 (kappa = 0.290).…”
Section: Discussioncontrasting
confidence: 77%
“…However, quantitative urine culture is laborious and requires a longer period to complete. Consequently, in most primary care settings, the use of a single (most often dipstick) or rarely two of these protocols without quantitative urine culture is often relied upon for clinical laboratory diagnosis of UTI [6, 7]. Urine culture is most often requested only when a patient is having a recurrent infection or when symptoms are quite severe.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of nitrites is highly predictive of UTI, but their absence does not exclude it. In a marked contrast, a higher sensitivity of 90% for NIT+ alone, was reported by Sirasaporn et al among 56 spinal code injury patients (SCI) in Thailand [29]. While UTI in the general population is based on symptoms, urinalysis and culture, this approach is not applicable to SCI patients as they already have an impaired neurological function and urinary system[30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative urine culture, on the other hand, takes more time and effort to finish. For this reason, the use of one (typically dipstick) or very infrequently two of these protocols without quantitative urine culture is frequently relied upon for clinical laboratory diagnosis of UTI in most primary care settings [7,8]. Most of the time, a urine culture is only ordered when a patient has quite severe symptoms or a recurring infection.…”
Section: Introductionmentioning
confidence: 99%